SARS-CoV-2: Emerging Role in the Pathogenesis of Various Thyroid Diseases - Murugan AK; Alzahrani AS (Dove Medical Press, 2021)
Avaniyapuram Kannan Murugan,1 Ali S Alzahrani1,2 1Division of Molecular Endocrinology, Department of Molecular Oncology, King Faisal Specialist Hospital and Research Centre, Riyadh, 11211, Saudi Arabia; 2Department of Medicine, King Faisal Specialist Hospital and Research Centre, Riyadh, 11211, Saudi ArabiaCorrespondence: Avaniyapuram Kannan MuruganDivision of Molecular Endocrinology, Department of Molecular Oncology, King Faisal Specialist Hospital & Research Centre, Riyadh, 11211, Saudi ArabiaTel +966 11-4647272 Extn 35076Email akmurugan@gmail.comAbstract: Coronavirus disease-2019 (COVID-19) is asymptomatic in most cases, but it is impartible and fatal in fragile and elderly people. Heretofore, more than four million people succumbed to COVID-19, while it spreads to every part of the globe. Severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) induces various dysfunctions in many vital organs including the thyroid by utilizing ACE2 as a receptor for cellular entry. Emerging reports clearly show the involvement of SARS-CoV-2 in diverse thyroid disorders. Thus, this review article aims to review comprehensively all the recent developments in SARS-CoV-2-induced pathogenesis of thyroid diseases. The review briefly summarizes the recent key findings on the mechanism of SARS-CoV-2 infection, the role of ACE2 receptor in viral entry, SARS-CoV-2-activated molecular signaling in host cells, ACE2 expression in the thyroid, cytokine storm, and its vital role in thyroid dysfunction and long-COVID in relation to thyroid and autoimmunity. Further, it extensively discusses rapidly evolving knowledge on the potential part of SARS-CoV-2 in emerging various thyroid dysfunctions during and post-COVID-19 conditions which include subacute thyroiditis, Graves' diseases, Hashimoto's thyroiditis, thyrotoxicosis, and other recent advances in further discerning the implications of this virus within thyroid dysfunction. Unraveling the pathophysiology of SARS-CoV-2-triggered thyroid dysfunctions may aid pertinent therapeutic options and management of these patients in both during and post-COVID-19 scenarios.Keywords: thyroid, COVID-19, hyperthyroidism, hypothyroidism, SARS-CoV-2, ACE2, inflammation, IL6, subacute thyroiditis, Graves' disease, Hashimoto's thyroiditis, thyrotoxicosis, p38/MAPK, thyroid cancer